Room-Temperature Quantum Diodes with Dynamic Memory for Neural Logic Operations - Kumar, Mohit; Park, Jiyeong; Kim, Junmo; Seo, Hyungtak (ACS Applied Materials and Interfaces, 2023)
The pursuit of high-performance, next-generation nanoelectronics is fundamentally reliant on exploiting quantum phenomena such as tunneling at room temperature. However, quantum tunneling and memory dynamics are governed by two conflicting parameters: the presence or absence of defects. Therefore, the integration of both attributes within a single device presents substantial challenges. Nevertheless, successful integration has the potential to prompt crucial breakthroughs by emulating biobrain-like dynamics, in turn enabling sophisticated in-material neural logic operations. In this work, we demonstrate that a conformal nanolaminate HfO2/ZrO2 structure on silicon enables high-performing (>106 s) Fowler-Nordheim tunneling at room temperature. In addition, the device exhibits unipolar dynamic hysteresis loop opening (on/off ratio >102) with high endurance (>104 cycles) along with negative differential resistance, which is attributed to the collective ferroelectric and capacitive effects and is utilized to emulate synaptic functions. Further, proof-of-concept logic gates based on voltage-dependent plasticity and time-domain were developed using a single device, offering in-material neural-like data processing. These findings pave the way for the realization of high-performing and scalability tunneling devices in advanced nanoelectronics, which mark a promising route toward the development of next-generation, fundamental neural logic computing systems.
Keywords: Dynamic hysteresis loops; Dynamic memory; Fowler-Nordheim tunneling; Logic operations; Nano-laminates; Neural logic; Performance; Quantum memory; Quantum phenomena; Quantum tunneling; diodes; ferroelectric; neural logic; quantum tunneling; room temperature